(untitled) (Physical Education, Health and Social Sciences, 2026)
This study investigates the impact of Artificial Intelligence (AI) writing tools, particularly ChatGPT, on the writing skills of English as a Second Language (ESL) students in Pakistani universities. The rapid integration of generative AI into higher education has transformed academic writing practices by offering students instant feedback on grammar, coherence, vocabulary, organization, and idea development. However, concerns regarding overdependence, plagiarism, reduced critical thinking, and academic integrity remain significant. This mixed-method research focuses on three public universities in Sindh: the University of Sindh, Jamshoro; Mehran University of Engineering and Technology (MUET), Jamshoro; and Shaheed Benazir Bhutto University (SBBU), Nawabshah. The study aims to examine how AI writing tools influence students’ writing proficiency, explore students’ and teachers’ perceptions regarding their academic use, and identify institutional challenges in integrating such tools responsibly. Quantitative data were collected through structured questionnaires from 300 undergraduate ESL students and analyzed using SPSS including descriptive statistics, correlation, and regression analysis. Qualitative data were obtained through semi-structured interviews with 15 teachers and 15 students and analyzed using thematic analysis. Findings indicate that AI tools positively affect grammar accuracy, vocabulary development, confidence, and drafting efficiency. Students reported reduced writing anxiety and improved revision practices. However, excessive dependence on AI-generated content negatively affected originality and critical engagement with writing tasks. Teachers emphasized the need for AI literacy policies and guided classroom use rather than complete restriction. Triangulation confirmed that AI tools function best as support mechanisms rather than replacements for student writing. The study recommends structured institutional guidelines, faculty training, ethical AI usage policies, and curriculum integration models to maximize pedagogical benefits while minimizing risks. The findings contribute to current debates on AI-assisted writing in ESL education within Pakistani higher education.